Jméno společníka jako součást obchodní firmy - Jarmila Pokorná; Eva Večerková (Časopis pro Právní Vědu a Praxi, 2015)
The article deals with legal regulation of using partners names in the firm names of business companies. It is looking into the problem of giving and  taking back consent to use the name of natural person in the firm of business company. The new Civil Code makes use of the name dependent on special relation between business company and natural person and on permission of natural person, but it does not provide how and when the permission should be given. By definition, there has to be a contract between bearer of  he name and the company, the contract can  also form a part of articles of association. If the bearer of the name dies, a permission can be given by his husband or descendant or ancestor. The person being authorized to give a permission can take the permission back, if circumstances have changed significantly. However, it is still unclear, how to proceed in case of large number of authorized persons.